A Subscription vs. Appropriation Framework for Natural Resource Conflicts - Dripto Bakshi; Indraneel Dasgupta (Institute of Labor Economics (IZA), 2020)
We examine how cross-community cost or benefit spillovers, arising from the consumption of group-specific public goods, affect both inter-group conflicts over the appropriation of such goods and decentralized private provision for their production. Our model integrates production versus appropriation choices, vis-à-vis group-specific public goods, with their decentralized voluntary supply, against a backdrop of such cross-community consumption spillovers. Our flexible and general formulation of consumption spillovers incorporates earlier specifications as alternative special cases. We show that stronger negative (or weaker positive) consumption spillovers across communities may reduce inter-group conflict and increase aggregate income (and consumption) in society under certain conditions. Thus, stronger negative consumption spillovers may have socially beneficial consequences. We also identify conditions under which their impact will be both conflict-augmenting and income-compressing. Our general theoretical analysis offers a conceptual structure within which to organize investigation of feedback loops linking ethnic conflict and natural resource degradation in developing country contexts.
Keywords: D72; D74; O10; O20; 330; public good contest; natural resource conflict; production versus appropriation; public bad; rent-seeking